Female Regency Rule in Western Pomerania Exemplified by Duchess Elizabeth, the Wife of Warcisław IV (1326–ca. 1350) - Patrycja Jędrzejewska-Michalak (Studia Maritima)
Princess Elizabeth, wife of Wartislaw IV, Prince of Wolgast, was one of the most publicly active women in Western Pomerania. After her husband died in 1326, Elizabeth had to face the function of regent because her sons were minors. When she took over, she exercised power and fought to maintain the principality using various methods. The text is intended to show in particular the situation in which the Duchess of Pomerania found herself after the death of her husband and the difficulties she had to face to maintain the inheritance of Wartislaw IV for her sons. An important aspect is also the presentation of how Elizabeth dealt with the problems she encountered during her rule, as well as the assessment of her actions. The source base consists mainly of selected documents that the duchess exhibited or co-exhibited with her sons.